Immediate oral rehabilitation using dental implants after marginal mandibulectomy: A case report - Ribeiro, Paulo Domingos; Momesso, Nataira Regina; Marques Padovan, Luis Eduardo; Oreadi, Daniel; Matsumoto, Mariza Akemi [UNESP] (American Academy of Implant Dentistry, 2020)
Mandibular reconstruction techniques are always a challenge to oral and maxillofacial (OMF) surgeons. Techniques and treatment plans that offer the patient OMF rehabilitation should always be available. Technological innovations have enabled more rapid, safer, and more secure treatment than in the past. This article describes a case using a different approach. The patient was treated with marginal mandibulectomy and immediate rehabilitation with osseointegrated implants; a hybrid prosthesis was fabricated a short time thereafter. This treatment plan demonstrated its utility and efficiency in this case. An approach with fewer surgeries and OMF rehabilitation needs be considered in all cases.
Keywords: Ameloblastoma; Dental implants; Immediate loading; Oral rehabilitation